Hadis-Hadis Tentang Pendidikan:Suatu Telaah tentang Pentingnya Pendidikan Anak - Susan Noor Farida (Diroyah : Jurnal Studi Ilmu Hadis, 2016)
It is very important in shaping the nature and character of man to be perfect man is education. Through education, be it family, school, or neighborhood, people can open mind for instance that there is nothing in the universe, there are a lot of science. From the start that there is in humanity itself up space that is difficult to reach by the senses and in the end thinking that the universe is the creator and owner.among the rule was one of a child's education should be noted that education in childhood that will affect the character of the child as an adult later. Education of children is not only done when they are still small. But, carried in the womb until he grew up. Hadith  as part of the essential teachings of islam have so many precious cargo that can be used as a foothold in the education of children of this discourse. Therefore, the authors will describe some of the hadith related to the education of children